Characterization of urethritis-associated Neisseria meningitidis isolated from men who have sex with women in China. Issue 5 (May 2022) - Liu, Wugao; Zhou, Shuxin; Wang, Wei; Lin, De; Chu, Weihua
Highlights: Meningococci were detected in urethral specimen from men oral sex with woman. Urethral infection is caused by Neisseria meningitidis . Results indicated that female-to-male transmission of meningococci can occur through oral-genital sex.